2015
DOI: 10.17344/acsi.2014.1135
|View full text |Cite
|
Sign up to set email alerts
|

Bioacid Hydroconversion over Co, Ni, Cu Mono- and Indium-doped Bimetallic Catalysts

Abstract: Caprylic acid (CA) as model reactant was selectively reduced in a flow-through reactor in hydrogen stream at 21 bar total pressure and 240-360°C over alumina loaded with the adjacent Co, Ni, Cu host and In guest metals. The main target of this research is the recognition of efficient cobalt catalysts for carboxylic group hydroconversion compared to more familiar nickel and copper composites. The catalysts were activated in H 2 flow at 21 bar and 450°C. By variation of main metal or modification with indium, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Harnos, Onyestyák and co‐workers investigated combination of supported Ni and In 2 O 3 in gas‐phase hydrogenation of carboxylic acids such as octanoic acid, acetic acid and decanoic acid to the corresponding alcohols (Table , entries 1–7), and they found that modification of Ni metal with In 2 O 3 improved selectivity and activity. Also, the performance was superior to the Adkins catalyst, a standard catalyst of Cu−Cr type catalyst for hydrogenation of carboxylic acid and esters.…”
Section: Heterogeneous Catalysts With Bimetallic Speciesmentioning
confidence: 99%
“…Harnos, Onyestyák and co‐workers investigated combination of supported Ni and In 2 O 3 in gas‐phase hydrogenation of carboxylic acids such as octanoic acid, acetic acid and decanoic acid to the corresponding alcohols (Table , entries 1–7), and they found that modification of Ni metal with In 2 O 3 improved selectivity and activity. Also, the performance was superior to the Adkins catalyst, a standard catalyst of Cu−Cr type catalyst for hydrogenation of carboxylic acid and esters.…”
Section: Heterogeneous Catalysts With Bimetallic Speciesmentioning
confidence: 99%
“…When compared against the parent monometallic catalyst, a systematic suppression of the hydro-decarbonylation reaction was found. [39][40][41] By analogy, we propose that indium poisons the surface of metallic cobalt, hindering its total hydrogenation activity (approximately 80% CO2 conversion on metallic Co vs. 19% on In@Co-1). This surface modification may also prevent methane formation due to a slower hydrogenolysis rate of the C-O bond compared to the desorption rate of the CO and CH3OH intermediates.…”
Section: Figure 4 Adf-stem Imaging and Elemental Mapping Of Metallic mentioning
confidence: 99%